Development of Religious Moral Values in Early Childhood Through Exemplary Storytelling Activities at Darul Arifin Islamic Kindergarten, Jambi City - Nur Anisyah; Anisah; Siti Marwah (Journal Of Social Siences And Islamic Studies (JOSIS), 2026)
This research aims to explore the development of religious moral values in early childhood through exemplary storytelling activities at one single school : Darul Arifin Islamic Kindergarten in Jambi City. Early childhood represents a critical phase in the formation of character and moral values. Through the storytelling method, children can internalize the moral messages embedded within exemplary narratives. This study employs a qualitative approach, with data collection techniques encompassing observation, interviews, and documentation analysis. The informants in this research comprised three primary groups: teachers, parents, and the participating children at Darul Arifin Islamic Kindergarten.  The findings indicate that storytelling activities not only enhance children's comprehension of religious values but also bolster their social and emotional competencies. Consequently, such activities can serve as an effective strategy for character education within early childhood educational settings.